Mild intermittent hypoxia may improve autonomic dysfunction in persons living with spinal cord injury: a preliminary snapshot - Soltesz, Alexandra E.; Zhao, Fei; Wecht, Jill M.; Mateika, Jason H.; Panza, Gino S. (Frontiers in Neuroscience, 2025)
Persons with spinal cord injuries often suffer from autonomic dysfunction, sleep disordered breathing, and impaired mitochondrial capacity. Current treatment options for these individuals are limited and often have significant side effects. Thus, new interventions that target multiple physiological systems and circumvent physical limitations would be a significant development for persons with spinal cord injury (pwSCI). One potential intervention is daily mild intermittent hypoxia (MIH) which has been shown to improve blood pressure control and upper airway function during sleep. Four individuals with chronic motor incomplete SCI underwent 8 days of MIH (ClinicalTrials.Gov ID #NCT05351827, https://clinicaltrials.gov/study/NCT05351827). The MIH protocol was administered each morning during wakefulness with end-tidal oxygen maintained at 55–60 mmHg. End-tidal carbon dioxide was maintained at + 3 mmHg above baseline during the MIH. Autonomic dysfunction (autonomic dysreflexia and orthostatic hypotension), sleep quality, upper airway function, mitochondrial capacity, and microvascular function were tested before, the day after, and 2 weeks following the MIH protocol. Systolic autonomic dysreflexia improved by 46% ± 14% and orthostatic hypotension improved by 160% ± 63% after MIH. Reductions in the apnea hypopnea index were observed, alongside a concurrent reduction in arousals during sleep. Upper airway function improved and mitochondrial capacity increased following 8 days of MIH. These preliminary data from four participants in an ongoing clinical trial suggest that 8 days of MIH may improve autonomic dysfunction, sleep quality, and mitochondrial capacity in pwSCI. The recruitment of additional participants is required to support these preliminary findings.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05351827, identifier NCT05351827.